You are a star, Jane Goodall - Robbins, Dean, 1957-; Aly, Hatem (2022)
"Using a unique mix of first-person narrative, hilarious comic panels, and essential facts, Dean Robbins introduces young readers to an scientific trailblazer. The second book in an exciting new nonfiction series, You Are a Star, Jane Goodall focuses on Jane's lifelong mission to understand the chimpanzees and protect the planet. Hatem Aly's spot-on comic illustrations bring this icon to life, and engaging back matter instructs readers on how to be more like Jane!"--
Includes bibliographical references.
Ages 5-7.
Grades K-1.
Keywords: Goodall, Jane, -- 1934- -- Juvenile literature; Primatologists -- England -- Biography -- Juvenile literature; Chimpanzees -- Tanzania -- Gombe National Park -- Juvenile literature; JUVENILE NONFICTION / Biography & Autobiography / Science & Technology; JUVENILE NONFICTION / Biography & Autobiography / Women